2021
DOI: 10.3389/fnut.2021.683369
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Weight Loss, and Weight Maintenance in the DiOGenes Multicenter Trial

Abstract: In this secondary analysis of the DiOGenes study, we investigated whether physical activity (PA) contributes to diet-induced weight loss and helps to reduce subsequent regain. We also studied the associations of PA with changes in cardiometabolic variables. Adults with overweight were included and followed an 8-week low-calorie diet (LCD). When successful (>8% weight loss), participants were randomized to different ad libitum diet groups and were advised to maintain their weight loss over the 6-month in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…More specifically, we observed a sustained loss of fat mass, which has, for example, been observed in the DiOGenes trial in adults with overweight or obesity 6 months after an 8‐week low‐calorie diet. However, the loss of fat‐free mass in that study was about 20% of the body weight lost 27 . To our knowledge, sustained fat mass loss with maintained or improved lean mass has not been reported before in older adults with obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…More specifically, we observed a sustained loss of fat mass, which has, for example, been observed in the DiOGenes trial in adults with overweight or obesity 6 months after an 8‐week low‐calorie diet. However, the loss of fat‐free mass in that study was about 20% of the body weight lost 27 . To our knowledge, sustained fat mass loss with maintained or improved lean mass has not been reported before in older adults with obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 54%
“…However, the loss of fat-free mass in that study was about 20% of the body weight lost. 27 To our knowledge, sustained fat mass loss with maintained or improved lean mass has not been reported before in older adults with obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 75%
“…The authors suggested that non-adherence or lack of willpower are exclusive among PwO is false and this belief may perpetuate weight bias and stigma [27]. In a secondary analysis of the DiOGenes study, they found that higher selfimposed levels of physical activity may improve the cardiometabolic risk profile during weight loss and help maintain weight loss in the long term [28]. Moreover, in a systematic review and metanalysis they found that the increase in physical activity is the most consistent positive correlate of weight loss maintenance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions are currently used to manage weight in cases of obesity, which usually focused on implementing lifestyle changes that include physical activity and dietary recommendations [9], [33]- [35]. Nevertheless, there are mixed evidence on the effectiveness of these interventions [7], [36]- [40] which remains a major challenge in the fight against obesity especially in SSA. Additionally, there is paucity of studies on the obesity and the effectiveness of the available obesity interventions in SSA [38], [41]- [46].…”
Section: Rationalementioning
confidence: 99%